2018
DOI: 10.1021/acs.jafc.8b00250
|View full text |Cite
|
Sign up to set email alerts
|

Improved Analytical Method for Determination of Cholesterol-Oxidation Products in Meat and Animal Fat by QuEChERS Coupled with Gas Chromatography–Mass Spectrometry

Abstract: Cholesterol is widely present in animal fats and meat products and can undergo oxidation to form cholesterol-oxidation products (COPs) during heating. The objective of this study was to develop a QuEChERS method for the determination of COPs in edible animal fats and meat products via gas chromatography-mass spectrometry in which the required solvent volume and extraction time were reduced. By employing a DB-5MS capillary column (30 m × 0.25 mm i.d., 0.25 μm film thickness) and a temperature-programming method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 42 publications
(110 reference statements)
4
34
0
Order By: Relevance
“…During storage, the content of 5α,6α‐epoxycholesterol increased from 0.0005 to 0.0014 mg g −1 . This study demonstrated the presence of COPs in fresh and stored buttermilk, in addition to the influence of time on modulating their respective concentrations …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During storage, the content of 5α,6α‐epoxycholesterol increased from 0.0005 to 0.0014 mg g −1 . This study demonstrated the presence of COPs in fresh and stored buttermilk, in addition to the influence of time on modulating their respective concentrations …”
Section: Resultsmentioning
confidence: 99%
“…In fresh, unheated butter, none of the cholesterol oxides were found (Table ). Other researchers such as Chiu et al, reported that fresh butters can contain traces of cholesterol oxidation products with total content reaching 0.000526–0.00136 mg g −1 . Cais‐Sokolińska & Rudzińska found that fresh buttermilk contains approximately 0.002 mg of total cholesterol oxides per g of fat.…”
Section: Resultsmentioning
confidence: 99%
“…GC and HPLC are the most widely used techniques for the analysis of COPs. GC–MS is the most accurate and commonly applied quantification method for these kinds of compounds, giving highly promising results [132,133]. The experimental procedure involves lipid extraction, saponification, purification and derivatization in order to enhance their volatility and thermal stability and to reduce contaminants (traces of cholesterol and/or partial glycerides) [134].…”
Section: Methods For the Measurement Of Compounds Derived From Lipmentioning
confidence: 99%
“…Blood cholesterol level is determined by dietary fat and cholesterol intake and the body's cholesterol biosynthesis and excretion (5). Endogenous synthetic cholesterol accounts for nearly 70%, whereas the remaining 30% amount is mainly derived from animal products (6). Pork products are rich in cholesterol ranging from 57 mg/100 g in loin to 116 mg/100 g in dewlap (7).…”
Section: Introductionmentioning
confidence: 99%